The Effects of Mixed Membership in a Deliberative Forum: The Irish Constitutional Convention of 2012–2014. (February 2020) - Farrell, David M; Suiter, Jane; Harris, Clodagh; Cunningham, Kevin
The Constitutional Convention was established by the Irish government in 2012. It was tasked with making recommendations on a number of constitutional reform proposals. As a mini-public, its membership was a mix of 66 citizens (randomly selected) and 33 politicians (self-selected). Its recommendations were debated on the floor of the Irish parliament with three of them leading to constitutional referendums; other recommendations are in the process of being implemented. This article uses data gathered during and after the operation of the Convention to examine this real-world example of a mixed-membership mini-public. The focus is on how the inclusion of politicians may have impacted on the Convention's mode of operation and/or its outcomes. We find little impact in terms of its operation (e.g. no evidence that politicians dominated the discussions). There is evidence of a slight liberal bias among the politician membership, but this had little effect on the outcomes.